2015
DOI: 10.1371/journal.pone.0140851
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Recording Urethral Pressure Profiles in Female Rats

Abstract: AimsUrethral pressure profile (UPP) and leak-point pressure (LPP) measurements as well as external urethral sphincter (EUS) electromyography (EMG) and videourodynamic analyses are the primary methods for evaluating urethral function in humans. However, UPP recording in female rats, a widely used animal model, is challenging due to their small body sizes. This study reports a novel method for recording UPP in female rats.Materials and MethodsSeventeen anesthetized female rats were studied. LPP data for 14 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Pressure measurements were more inconsistent 3 cm away distal to the injection site (close to the distal urethra). An in vivo study by Xu et al collected urethra pressure profiles with female rats at different locations of the urethra. The data revealed higher pressure inconsistencies near distal urethra as compared to the proximal urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure measurements were more inconsistent 3 cm away distal to the injection site (close to the distal urethra). An in vivo study by Xu et al collected urethra pressure profiles with female rats at different locations of the urethra. The data revealed higher pressure inconsistencies near distal urethra as compared to the proximal urethra.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to determine whether this complex pattern of structural elements could be correlated with any functional characteristics, measurements of urethral wall compliance were made along its length (see Xu et al, and legend Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The approach used was adapted from the method described by Xu et al, () to measure urethral pressure profiles. However, it is argued here that the method actually measures the compliance of the wall rather than the intrinsic pressure generated within the wall.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, compared with SCC, the method of optimized transurethral cystometry is easy to use by researchers. In addition, no record of UPP measurement in mice was found and only one early study showed a similar method for the UPP record in female rats . We present a novel method for recording UPP in female mice.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we propose that the UPP measurement could be used to measure the establishment of mice partial bladder outlet obstruction (pBOO) model. Early study proposed a method of testing the UPP in rats, and it is still challenging to record UPP in mice.…”
Section: Introductionmentioning
confidence: 99%